25 Personalising remote care in the home with intelligent everyday items: ideating with children and young people with lived experiences of healthcare. (15th December 2021) - Visram, Sheena; Leyden, Deirdre; Bappa, Dauda; Conner, Sue; Molyneux, Gemma; Sridharan, Shankar; Sebire, Neil J
Abstract : Introduction: The Internet of Things (IoT) has emerged as a disruptive technology with potential to revolutionise healthcare by collecting and communicating healthcare data from the home. This could enable health-related data to be remotely monitored for paediatric patients with long-term conditions. However, to anchor trust in new and remote digital care approaches, this requires involving patients as part of the design and evaluation process. Method: Members of the Great Ormond Street Hospital for Children's (GOSH) Young Persons' Advisory Group for research (YPAG), who typically have lived experiences of healthcare, were invited to a one-hour design workshop, to discuss common indicators of falling unwell, followed by imagining scenarios for intelligent everyday items in the home to help monitor wellness. Qualitative contributions were collected on a collaborative platform as micronarratives of 250 characters or less, anonymously, and voluntarily, and analysed for emergent themes. Results: 22 YPAG members, aged 10–21 years of age, contributed 51 comments on 3 behavioural indicators of falling unwell (i) pronounced lethargy (ii) feeling antisocial and (iii) reduced appetite. Correspondingly, intelligent home devices to track wellness were described as: (i) smart appliances: fridges to track changes in eating habits, (ii) smart garments: smart shoes, beds, and fabrics to track movement and clinical markers (iii) smart behavioural nudges: smart bottles that encourage good hydration (iv) digital biomarkers: smart nail clippers, tissues, and combs to track nutrient deficiencies and (v) smart sensors integrated into medical devices: inhalers, spirometers, and stethoscopes. Conclusion: In this exploratory workshop we ideate with the YPAG on whether data from intelligent everyday items in the home has potential to monitor wellness in the future. We recommend that future research in this growing field includes children and young people and that forums such as GOSH's YPAG are positioned well to deliberate the future of smart-home remote monitoring.